2019
DOI: 10.5897/ajbm2018.8735
|View full text |Cite
|
Sign up to set email alerts
|

Does the IFRS 15 impact earnings management? Initial evidence from Italian listed companies

Abstract: The purpose of the present work was to gauge the extent of the impact on earnings management derived from the adoption of International Financial Reporting Standards (IFRS) 15 as well as detecting whether the impact will be similar in different industries. To provide empirical evidence that earnings management is more frequent in some industries and less frequent in others by means of a statistical analysis, a sample of Italian listed companies in the period 2001-2017 was observed. Specifically, companies belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
0
7
0
5
Order By: Relevance
“…Empirical studies on management practice and IFRS are focused on aggregate accrual models (Grecco, 2013;Joia & Nakao, 2014;Marçal & Macedo, 2019) and others relating earnings management to the revenue standard (Baldissera et al, 2018;Tutino et al, 2019;Souza et al, 2022;Dias et al, 2023). From new analytical perspectives, other studies have advanced in measuring management levels using new empirical models of specific revenue accruals to analyze the effects of adopting the new revenue recognition standard.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies on management practice and IFRS are focused on aggregate accrual models (Grecco, 2013;Joia & Nakao, 2014;Marçal & Macedo, 2019) and others relating earnings management to the revenue standard (Baldissera et al, 2018;Tutino et al, 2019;Souza et al, 2022;Dias et al, 2023). From new analytical perspectives, other studies have advanced in measuring management levels using new empirical models of specific revenue accruals to analyze the effects of adopting the new revenue recognition standard.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Given the flexibility and discretion over recognizing the revenue brought by the standard, there was more research on analyzing the effects of earnings management models by accruals. Tutino et al (2019) found an increase in the levels of earnings management after adopting IFRS 15 in Italian companies, while Souza et al (2022) showed an increase in earnings management and a decrease in the earnings quality after adopting IFRS 15 in companies in the Brazilian capital market. On the other hand, Dias et al (2023) did not identify significant effects after adopting CPC 47 in Brazilian companies.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the IFRS 15 adoption, many entities will change the total contractual considerations measurement and its split among the several elements deliverable in a single contract (Berchowitz & Whitehead, 2014). The IFRS 15 introduction's possible effects could differ in each industry (Tutino et al, 2019). Therefore, entities applying PSAK 72 must begin to analyze the impact of IFRS 15 or PSAK 72 on their business, including taxation (Oncioiu & Tănase, 2016).…”
Section: Issues Concerning Income Taxmentioning
confidence: 99%
“…Thus, even with a unique set of high quality accounting standards (IFRS) and strong reporting incentives, countries' specific characteristics still play an important role in the way IFRS is implemented in each country. (Marco et al 2019) "Does the IFRS 15 impact earnings management? Initial evidence from Italian listed companies" The purpose of the research present work was to gauge the extent of the impact on earnings management derived from the adoption of International Financial Reporting Standards (IFRS) 15 as well as detecting whether the impact will be similar in different industries.…”
Section: Earning Management and International Financial Reporting Standard (Ifrs)…mentioning
confidence: 99%